Influence of Incentives on Performance in a Pre-College Biology MOOC - Jiang, Suhang; Williams, Adrienne E.; Warschauer, Mark; He, Wenliang; O'Dowd, Diane K. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2014)
There is concern that online education may widen the achievement gap between students from different socioeconomic classes. The recent discussion of integrating massive open online courses (MOOCs) into formal higher education has added fuel to this debate. In this study, factors influencing enrollment and completion in a pre-college preparatory MOOC were explored. University of California at Irvine (UCI) students of all preparation levels, defined by math Scholastic Aptitude Test (SAT) score, were invited to take a Bio Prep MOOC to help them prepare for introductory biology. Students with math SAT below 550 were offered the explicit incentive of an early change to the biology major upon successful completion of the MOOC and two additional onsite courses. Our results demonstrate that, among course registrants, a higher percentage of UCI students (>60%) completed the course than non-UCI registrants from the general population (<9%). Female UCI students had a greater likelihood of enrolling in the MOOC, but were not different from male students in terms of performance. University students entering with low preparation outperformed students entering who already had the credentials to become biology majors. These findings suggest that MOOCs can reach students, even those entering college with less preparation, before they enter university and have the potential to prepare them for challenging science, technology, engineering, and mathematics (STEM) courses.